Pengaruh Moralitas Pajak, Kesadaran Pajak, dan Budaya Pajak Terhadap Kepatuhan Pajak UMKM - Jenny Jenny; Meilie Ratanacitta Exeliem; Deni Darmawati (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the effect of tax morality, tax awareness, and tax culture on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) in West Jakarta. This research employs a quantitative approach using primary data collected through questionnaires distributed to 100 MSME taxpayers selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that tax morality, tax awareness, and tax culture have a positive and significant effect on MSME tax compliance, both partially and simultaneously. These findings suggest that improving MSME tax compliance requires strengthening moral values, enhancing tax awareness, and fostering a positive tax culture.